ESCAPING THE RESOURCE CURSE: A COMPARATIVE ANALYSIS OF INDONESIA AND NIGERIA IN THE CONTEXT OF NATURAL RESOURCE PRIVATIZATION - Rizky Bangun Wibisono; Nazilatus Sholikhah; Anggun Nadya Dinata; M Arvin Kirano; M Haris Ramdani (Fakultas Politik Pemerintahan, 2025)
Abstract This study investigates the political instability triggered by the privatization of natural resources in Indonesia, particularly through Government Regulation No. 72/2016, using Nigeria as a comparative case. Employing a qualitative, descriptive-comparative approach and case studies in Papua, Sulawesi, and the Niger Delta, the research finds that non-inclusive resource governance, weak state oversight, and the dominance of foreign corporate actors have led to local marginalization, social inequality, and conflict. The Nigerian case illustrates how overreliance on oil, extreme privatization, and poor governance have entrenched the resource curse—manifesting in poverty, political crisis, and armed violence. This study underscores the risks Indonesia faces as it exhibits early signs of similar vulnerabilities, including agrarian disputes, environmental degradation, and diminishing state control over strategic sectors. The paper calls for inclusive governance reforms, greater public participation, and a critical reassessment of privatization policies to prevent escalating instability and ensure sustainable, equitable resource management. Keywords: Privatization, resource curse, inclusive governance.